IMPROVING STUDENTS’ LEARNING OUTCOME: IMPLEMENTATON MIND MAPPING METHOD WITH GOCONQR - Dewi Dewantara (JURNAL PENA SAINS, 2019)
This article aims to describe the improvement in student learning outcomes after applying to learn with the mind mapping method using the GoConqr application. This type of research is a quantitative descriptive. The sampling technique was purposive sampling, namely students who took the "Telaan Fisika SM III" at Lambung Mangkurat University 2018/2019 Academic Year. The number of research subjects is 15 students. Data collection techniques are using pretest and posttest. Data were analyzed using N-gain. N-gain test results obtained a value of 0.503. Therefore, it can be concluded that the effectiveness of learning with mind mapping methods using the GoConqr application is in the medium category. Thus, learning with the mind mapping method using the GoConqr application is effectively applied to improve student learning outcomes.